PT Pertamina (Persero)'s Perspective on the Development of Efforts to Empower SMEs in the Small Medium Enterprise Partnership Program (SMEPP) in the Jakarta Region - Maysa Syifa Aljauza; Sari Viciawati Machdum (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Companies must fulfill their Corporate Social Responsibility (CSR) in conducting business. One of the goals of CSR is to enhance the economy through empowering of MSMEs (Micro, Small, and Medium Enterprises). By empowering MSMEs, economic growth will be further enhanced. Some studies discussing "power" place more emphasis on the perspective of the beneficiaries. Meanwhile, the perspective of the service providers, in this case related to the private sector through CSR, has not yet been studied. Therefore, this research aims to examine Pertamina's perspective on the concept of power in the process of empowering MSMEs and Pertamina's efforts in empowering its partner MSMEs. This research uses qualitative descriptive method with a snowball sampling technique. The research results indicate that PT Pertamina views "power" from two perspectives: the pluralist perspective and the elite perspective. As part of its efforts to empower MSMEs, PT Pertamina implements the Small Medium Enterprises Partnership Program (SMEPP), which includes funding for MSMEs, mentoring and coaching through the UMK Academy, as well as the SMEXPO Marketplace and Exhibition.